Uma proposta de ensino de geometria construindo pipas - Motinaga, Esdras Henrique Regatti (Universidade Federal de São Carlos, 2013)
In this paper we propose a learning process using as a theoretical base called Didactic Engineering. Our proposal is to develop content from the flat geometry of a problem related to kites. Using as a theoretical framework Didactic Engineering Could explain some didactic variables allows us to have some control over the process of teaching and learning. The proposal is aimed at students from sixth grade of elementary school, but an analysis of the potential of working with the kites to develop content of geometry shows that it is possible to make adjustments to work with students from all levels of basic education.
Keywords: Geometria; Papagaio (brinquedo); Engenharia didática; Matemática - estudo e ensino; Educação básica; Geometria plana; Ensino fundamental; Construção de pipas; Didactic engineering; Plane geometry; Elementary school; Building kites; CIENCIAS EXATAS E DA TERRA::MATEMATICA